2023
DOI: 10.31235/osf.io/3y9u6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are we Safe? An Investigation on ‘Eve-teasing’ (or public sexual harassment) in India

Abstract: In recent years, many countries have tightened the rules against harassment at the workplace and violence in the home. On the other hand, the incidences of sexual harassment in public places have not been paid sufficient attention, specifically against women. Developing countries like India have recorded the increment of sexual harassment cases in public places due to the increment in participation of women in outside activities such as education and employment. In India, the term ‘Eve-teasing’ is a euphemism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…For example, Chairunnisa et al (2022) showed a high prevalence of sexual violence cases against female students, but the majority were reluctant to report. Victims' reluctance to Insufficient awareness and education compound the problem, while flawed legal systems and distrust in law enforcement (even at the university level) hinder the pursuit of justice (Noor & Iamtrakul, 2023;Rana, 2023). In recent years, there is a sexual harassment task force that has been established in several Indonesia universities.…”
mentioning
confidence: 99%
“…For example, Chairunnisa et al (2022) showed a high prevalence of sexual violence cases against female students, but the majority were reluctant to report. Victims' reluctance to Insufficient awareness and education compound the problem, while flawed legal systems and distrust in law enforcement (even at the university level) hinder the pursuit of justice (Noor & Iamtrakul, 2023;Rana, 2023). In recent years, there is a sexual harassment task force that has been established in several Indonesia universities.…”
mentioning
confidence: 99%